التقديم والتأخير (دراسة تحليلية فى بعض آيات القرآنية): ADVANCEMENT AND DELAY (ANALYTICAL STUDY IN SOME QURANIC VERSES) - Tauhid (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2021)
مستخلص البحث: يهدف هذا البحث ليصف عن التقديم والتأخير فى بعض الآيات القرآن. أما الطريقة المستخدمة هي الطريقة الوصفية على البحث المكتبى وهي بيان المعلومات منظما و واقعيا ومطابقا بالآيات التى فيها التقديم والتأخير. ونتائج البحث هي أن التقديم والـتأخير فى القرآن الكريم متنوعة صورته، منه التقديم والتأخير فى الاستفهام، والتقديم والتأخير بين الفعل والاسم فى الاستفهام التقريري، والتقديم والتأخير بين الفعل والاسم فى الاستفهام الإنكاري، والتقديم والتأخير فى الخبر، وأما أسرار التقديم والتأخير فى القرآن الكريم كثير منها ما قدم فى القرآ الكريم والمعنى عليه، وما قدم فى القرآن الكريم والنية به التأخير، وما قدم فى آية وأخر فى أخرى. الكلمات المفتاحية: التأخير، التقديم، أية القرآن Abstract: This research aims to describe the introduction and delay in some verses of the Qur’an. As for the method used, it is the descriptive method on the desk search, which is an organized and realistic statement of the information, in conformity with the verses in which the introduction and the delay. The results of the research are that the introduction and delay in the Holy Qur’an are of various forms, including the introduction and delay in the interrogative, the introduction and the delay between the verb and the noun in the declarative question, the present and the delay between the verb and the noun in the negative interrogation, the introduction and the delay in the predicate. As for the secrets of the introduction and delay in the Holy Qur’an, many of them What was presented in the Noble Qur’an and its meaning, and what was presented in the Noble Qur’an and the intention was to delay it, and what was presented in a verse and another in another.